Not even a recession: The great German gas debate in retrospect - Benjamin Moll; Moritz Schularick; Georg Zachmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
The German economy coped with the end of Russian gas and could have equally withstood an April 2022 cut-off. - Recently released GDP numbers confirm that the German economy withstood the end of Russian gas imports and even avoided slipping into a recession last winter. This outcome would seem to finally settle last year's debate on the effects of an end to Russian energy supplies triggered by the "What If" paper (Bachmann et al., 2022a). The short-run economic costs of severing the energy ties with Russia turned out to be moderate and manageable. The doomsday predictions of companies, industry associations and unions, and associated think tanks turned out to be far off the mark. The German government likely formulated policy on the basis of a substantial overestimation of the potential economic consequences of an end to Russian gas supplies. We show that, even with an earlier end to gas imports from Russia at the end of March 2022, Germany would have made it through the winter and would have exited the heating period with gas storage above critical levels. This analysis using data on gas imports and the gas storage situation at the end of the heating period settles the residual debate about the alleged importance of continuing gas imports after March 2022 until Russia stopped gas exports in August. Taking into account imports of Russian gas via third countries as well as re-exports, Germany imported about 100 TWh of gas from Russia between April and August 2022, and exited this winter's heating period with about 160 TWh of gas in storage. Assuming identical consumption and identical gas imports from third countries, German gas storage at the end of the winter would still have stood around 60 TWh or 25% even in a scenario in which Russian gas imports ended on 31 March 2022. Because a cut-off at the beginning of April would have coincided with the end of the previous heating period and a drop-off in household demand, gas supplies would have been sufficient at any point in time to satisfy both industrial and household gas demand. Shortages or rationing would have been avoided. Moreover, the country did not simply get lucky with particularly mild winter temperatures, as often alleged. The average winter temperature in the 2022/23 winter of 2.9°C was actually slightly colder than the average temperature over the four previous winters. On the contrary, negative shocks to energy supply such as the French nuclear and U.S. LNG shutdowns were substantial and complicated the adjustment.
Keywords: 330; Erdgaspolitik; Russisch; Sanktion; Wirkungsanalyse; Wirtschaftslage; Deutschland